Eugène Enriquez: Memory, Thinking and Humanity - Ludmila de V. M. Guimarães; Luciana O. Carreteiro (Clinical Sociology Review)
This article aims to provide an overview of the work on both personal and professional trajectory of the French thinker Eugène Enriquez who had a great influence on the creation and development of Clinical Sociology and French Psychosociology.  Enriquez legacy continues to inspire academicals and professionals through his innovative thinking and the depth of his oeuvre. The manuscript is divided into four parts. The first one emphasizes the author's socio-professional history, revealing personal aspects from birth to academic and intellectual consolidation as a pioneer in his field. In the second part, his three seminal works and their fundamental contributions are briefly presented. Herein, Enriquez adopts a psychosociological and clinical perspective to discuss social and organizational dynamics. His viewpoint significantly contributed to recognition of the interdisciplinarity between psychoanalysis and sociology.  In the third part, Enriquez most recent texts are discussed in which he analyzes society contemporary challenges, addressing social fragmentation and redefinition in human relations on the XXI century.  And finally, the last part engages on a personal narrative highlighting Eugène´s generosity and humanity.